EFFECT OF THE ADDITION OF GLASS BOTTLE PARTICLES ON THE MECHANICAL STRENGTHS OF COMPRESSED BLOCKS OF FIRED CLAY AND STABILIZED EARTH. - GBENONDE, S. G.; MILOHIN, Ggénondé S. G.; MILOHIN, Ggénondé S. G. (My University, 2017)
The valorisation of clayey soils in the civil construction and the recycling of the waste are current concerns of several countries like Benin. This study focuses on the development of compressed blocks made of stabilized earth and fired clay containing particles of glass bottles for their use in the building industry. After the characterization of the materials: clayey earth or laterite, clay and crushed glasses; the mechanical strengths of blocks in compression and in traction by flexural test (three-point bending test) were studied for various crushed glass contents ranging from 0 to 60%. In accordance with standard NF P 11-300, the earth soil studied is an A2ts soil and the clay is an A4 soil. The study of mechanical strengths has shown that at 21 days of age, the addition of 10% of crushed glasses induces a decrease of 10% of strength in traction by flexural test of the blocks stabilized with cement but a resistance gain of 17% in compression; the resistances are respectively 1.8 MPa against 2 MPa for the blocks without glasses in traction by three-point flexural test, and 5.3 MPa against 4.5 MPa, in compression. In addition, crushed glasses have a positive effect on strengths of fired clay blocks both in traction by flexural test and in compression. The strengths of the blocks with 10% of crushed glasses are higher than those of the blocks without glasses, and the maximum strength values are obtained at a dosage of 25% of crushed glasses with increase rates of 13% and 122% in traction by flexural test (8 MPa) and in compression (16.6 MPa) respectively.
Keywords: stabilized earth; fired clay; glasses; resistances.